On the projectile motion - Silva, Ricardo Parreira da (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2024)
Although the study of projectile motion after an oblique launch be a recurrent topic of consideration both in high school as well in junior disciplines of Calculus and Physics in college, its classical approach, in this context, presents it as a mere application of uniform motion and uniformly accelerated motion in two dimensions. Therefore, some of main properties as well interesting applications of this phenomenon are, in general, neglected. In this paper, we develop the basic theory of projectile motion, pointing out their main properties, and apply it to several non trivial and interesting problems that can be extended beyond the scope of this text, e.g. \cite{SS:04}.
Keywords: projectile launch; projectile motion; Galileu Galilei; Newton's Law